MANGANESE DIOXIDE BASED COMPOSITE ELECTRODES FOR ELECTROCHEMICAL SUPERCAPACITORS - Wang, Yaohui (My University, 2012)
Advanced electrodes based on MnO2 for the electrochemical supercapacitor (ES) application have been fabricated using electrochemical and chemical methods.
Electrosynthesis method has been utilized for the in-situ impregnation of manganese dioxide in commercial Ni plaque current collectors. Dipping-reduction, cathodic galvanostatic and reverse pulse electrosynthesis methods were investigated. The material loading was varied by the variation of the number of the dipping-reduction procedures in the chemical precipitation method or by the variation of charge passed in the electrochemical methods. The results obtained by different methods were compared. The dipping-reduction method offered the advantage of higher specific capacitances (SCs) at high scan rates, whereas other methods allowed higher material synthesis rate.
Cathodic electrolytic deposition (ELD) has been utilized for the fabrication of Ag-doped MnO2 films. The Ag-doped MnO2 films showed improved capacitive behavior and lower electrical resistance of 0.6 Ohm compared to pure MnO2 films. The highest SC of 770 F g-1 was obtained at a scan rate of 2 mV s-1 in the 0.5 M Na2SO4 electrolyte.
Electrodes for ES application were fabricated by cathodic electrodeposition of MnO2 on CNTs, which were grown by chemical vapor deposition on stainless steel meshes. The MnO2-CNT nanocomposites showed excellent capacitive behavior and low electrical resistance of 0.5 Ohm.
Electrophoretic deposition (EPD) has been utilized for the deposition of composite MnO2-multiwalled carbon nanotube (MWCNT) films for the ES application. Dopamine (DA), caffeic acid (CA), tyramine (TA), gallic acid (GA), polyacrylic acid (PAA) and pyrocatechol violet (PV) were shown to be effective and universal charging additives, which provide stabilization of MnO2 nanoparticles and MWCNTs in the suspensions. The influence of the structure of the organic molecules on their adsorption on the oxide nanoparticles has been investigated. We discovered that the number and site of OH group for dispersants were essential for the adsorption on oxide materials, and the number of aromatic ring was important for the adsorption on carbon materials. Pure CNT films were deposited using PV as a dispersant, which was the first time in literature to prepare pure CNT film using a dispersant. SCs decrease with increasing film thickness. SCs of composite MnO2-MWCNT obtained using EPD were in the range of 350-650 F g-1 depending on material loadings.
No comments. Thanks.
Keywords: electrochemical supercapacitor; energy storage; manganese dioxide; carbon nanotube; Other Materials Science and Engineering; Other Materials Science and Engineering